Effect of notch size on the fatigue damage behaviour of toughened epoxy adhesive specimens. Issue 1 (28th January 2017) - Beber, V. C.; Fernandes, P. H. E.; Schneider, B.; Brede, M.
ABSTRACT: In the present work the influence of notch size on the fatigue damage behaviour of toughened epoxy adhesive specimens is investigated. Notched and un-notched bulk adhesive specimens were fatigue tested at room temperature under tension-tension cyclic loading at a stress ratio of 0.1. The investigation was based on the analysis of fatigue life (SN) and stiffness degradation curves, which were correlated with notch size and applied stress. Finite element analysis (FEA) was carried out in order to evaluate the notch-dependent stress concentrations. Fatigue results evidenced a reduction of lifespan with increased applied stress amplitude and a possible relationship between the inverse slope of SN curves and notch size. Most notched samples exhibited lower fatigue strength in comparison to un-notched, except in the low cycle fatigue range where un-notched and notched samples had similar fatigue strength. Stiffness degradation showed a correlation with applied stress, i.e. an increase in applied stress was accompanied by faster and stronger degradation. For higher loads, un-notched and 0.2 mm notch samples presented greater stiffness degradation prior to failure than other notched samples.